2013
DOI: 10.1128/jb.00690-13
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Bacillus anthracis Secretome by the Immune Inhibitor A1 Protease

Abstract: The Bacillus anthracis secretome includes protective antigen, lethal factor, and edema factor, which are the components of anthrax toxin, and other proteins with known or potential roles in anthrax disease. Immune inhibitor A1 (InhA1) is a secreted metalloprotease that is unique to pathogenic members of the Bacillus genus and has been associated with cleavage of host proteins during infection. Here, we report the effect of InhA1 on the B. anthracis secretome. Differential in-gel electrophoresis of proteins pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 59 publications
2
37
0
Order By: Relevance
“…B. anthracis UM23C1-2 (pXO1 negative [pXO1 Ϫ ], pXO2 Ϫ ) secA calY null was used to purify InhA1 (14). E. coli TG-1 was the host for cloning.…”
Section: Blood Serum Mimic (Bsm)mentioning
confidence: 99%
See 1 more Smart Citation
“…B. anthracis UM23C1-2 (pXO1 negative [pXO1 Ϫ ], pXO2 Ϫ ) secA calY null was used to purify InhA1 (14). E. coli TG-1 was the host for cloning.…”
Section: Blood Serum Mimic (Bsm)mentioning
confidence: 99%
“…InhA1 was purified using a previously described method (14). InhA1 was expressed in B. anthracis strain UT357 cultured in LB medium for 16 h at 37°C.…”
Section: Blood Serum Mimic (Bsm)mentioning
confidence: 99%
“…The resulting vegetative cells spread in blood and other tissues as the causative agent of meningitis and ultimately causes death. Literature showed that among the secreted metalloproteases of B. anthracis, immune inhibitor A1 (InhA1) was found to be the single pathogenic member and during the infection it helps to cleave mammalian cell matter with addition to the modulation of the B. anthracis secreted proteins (Pflughoeft et al, 2014) and increases the permeability of blood-brain barrier resulting cerebral hemorrhages (Dhritiman et al, 2011). Previous investigation of Pflughoeft (2010) suggested that the protease cascade regulated the organism response in altering environments like reacting to a changing signal or in presence of different types of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The two proteases that have been the most studied, Npr599 and InhA, are metalloproteases that degrade extracellular matrix proteins, syndecan-1, and several proteins involved with fibrinolysis [107]. Interestingly, the secreted proteases InhA and HtrA also appear to regulate secreted B. anthracis proteins including the adhesin BslA [108][109][110]. B.…”
Section: The Vegetative Bacillimentioning
confidence: 99%
“…anthracis has several minor virulence factors that are thought to contribute to infection in addition to the exotoxin and capsule. These include proteases and cholesterol dependent cytolysins, which degrade host proteins or lyse immune cells, as well as other factors that reduce the inflammatory response to the bacteria [105][106][107][108][109][110][111][112][113][114][118][119][120]. One such immune modulating protein is the extracellular adenosine synthase A (AdsA) [121].…”
Section: Introductionmentioning
confidence: 99%